THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY STRATEGY IN MANAGEMENT SYSTEM ON BRAND PREFERENCE (STUDY CASE ON BANK MANDIRI BITUNG) - Omega, Gabriel Priskilla; Kindangen, Paulus (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: Corporate social responsibility (CSR) plays an important role in increasing the value of the company as a result of increased sales of the company by doing various social activities in the surrounding environment. The success of CSR in any organization depends on values correlation, social tendencies of the organization, and largely, the ethical tendencies. In this regard, banks are considered as the most sensitive organizations to CSR effects. The reason is that the banking industry is mainly responsible for those sectors of government which are more complicated and distinctive than the other economic sectors. The aim of this study is to know and analyze the CSR affects brand preference and how the commitment, reputation, and transparency variable influence brand preference on Bank Mandiri Bitung CSR programs. This research is a causal type of research through questionnaires and uses multiple regression analysis. 100 respondents are the sample size of this research. The result shows that the independent variable which is reputation and transparency has simultaneously influence brand preference as a dependent variable. The commitment variable shows that do not have a significant influence on the brand preference of Bank Mandiri Bitung.Keywords: corporate social responsibility, management system, brand preference.